Abdominal Aortic and Iliac Lesions Associated with Colaterals Aneurysms and Obstructions - de Sobregrau, Rafael; Viver, E; Ortiz, E; Rodríguez Mori, A.; Juan, J; de Frutos, L; Gutiérrez, J A (Cirugía del Uruguay, 1980)
Obliterating lesions in the aorto - il'iac sector and aneurysms in the abdominal aorta are in sone cases associated with lesions in the visceral arteries, especially in renal artery, and less in the upper mesentery and celiac trunk.